An Analysis Religion Values In The Novel Ground Zero By Agustinus Wibowo - Umar; Nursamsa Walkamar (Gudang Jurnal Multidisiplin Ilmu, 2023)
This research conducted by title analysis religion values in the novel ground zero by Agustinus Wibowo. This research were aimed (1) To analyze the religion values in the novel ground zero by Agustinus Wibowo; (2) To analyze the causes of religion values in the novel ground zero by Agustinus Wibowo. The method used was descriptive qualitative design. The source of the data is uses the primary data and secondary data. This research found that; (1) there was two kinds of religion value found in the ground zero novel namely; (1) positive religion valuethere are religion value of source of hope and optimism form that found on the data 01 and 21; promotes feelings of belongingness. This can be found on the data 3, 10, 12, 22, and 24; boosts self-esteem, and this can be found on the data 16, 17, and 25’ provides protection from existential threats. This can be found on the data 9, and 11; promotes healing of mind and body, this can be seen on the data 27; an improved mental and physical health, this data can be found on the data 20; encourages charity and altruism, this data can be found on the data 26; and (2) negative roles of religion. In this case, that content of anxiety created through scientific and religious views. This can be found on the data 34; content of bad religious programming on data 19; content of the data 34 too; rationalisation for hatred and prejudice. This can be found on the data 18; Power hungry religious leaders, this can be seen on the data 13, 14 and 16; segregation of humanity, this can be seen on the data 2, 5, 7, and 18. (2) The cause of Religion value those found by Agustinus Wibowo in his trip was religion symbol that had been found in the trip and about the people with different religion who had met with him along of way.